Interlocutions on Mental Health and Work: he Experience of Extension in The UFJF Medicine Course - de Miranda Ramos, Andréia Aparecida; Trevisan Zorzetto, Luis Henrique; Viana Costa, Amanda; de Oliveira Mota, Ana Carolina; Souza Silva, Caroline (Guará Journal, 2018)
The main purpose of the project is to address issues of mental health related to work and support patients with work-related mental disorders. It is carried out at the Regional Reference Center on Occupational Health of Juiz de Fora / MG and UFJF Medical School. Support and study groups are held monthly. The participants voluntarily register and are coordinated by medical students and the coordinator of the Project. All participants in the support group are transport workers diagnosed with work-related mental illness and associated orthopedic diseases. In the study group, the integration of professionals and students from different institutions takes place. Vignettes have been created on a radio program, in partnership between patients and the UFJF medical students. The groups have shown important space for understanding the process of mental illness and work, allowing the creation of new coping strategies as well as there has been a participation of participants in the group.